2016
DOI: 10.1155/2016/7286040
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Integrated Pest Management and Farmers Practices on Sustainable Environment in the Rice Ecosystem

Abstract: Integrated pest management (IPM) is an environmentally friendly technology. IPM is a multifaceted approach to pest management that seeks to minimize negative impacts on the environment. This technique is an important step towards providing healthy, viable food for a growing global population. The focus of this study was to examine the impact of integrated pest management in a rice agroecosystem. Currently, more than 80% of farmers rely on pesticides. IPM methods employed in our study had an impact on the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…Nonetheless, recent studies have indicated that ‘ Bt- cotton’ cultivars have been losing resistance against various insects [ 10 14 ]. Although Alam et al [ 34 ] reported that ‘ Bt -cotton’ cultivar ‘FH-634’ had the highest resistant to the sucking insects, we found that ‘FH-682’ was most resistant to jassid and had the highest susceptibility to whitefly. Shahid et al [ 35 ] found that cultivar ‘FH-118’ exhibited highest resistance to thrips, whereas cultivars ‘FH-17’, ‘FH-114’ and ‘FH-179’ proved most susceptible to thrips.…”
Section: Discussioncontrasting
confidence: 83%
“…Nonetheless, recent studies have indicated that ‘ Bt- cotton’ cultivars have been losing resistance against various insects [ 10 14 ]. Although Alam et al [ 34 ] reported that ‘ Bt -cotton’ cultivar ‘FH-634’ had the highest resistant to the sucking insects, we found that ‘FH-682’ was most resistant to jassid and had the highest susceptibility to whitefly. Shahid et al [ 35 ] found that cultivar ‘FH-118’ exhibited highest resistance to thrips, whereas cultivars ‘FH-17’, ‘FH-114’ and ‘FH-179’ proved most susceptible to thrips.…”
Section: Discussioncontrasting
confidence: 83%
“…Plianbangchang et al [25] and Alam et al [47] emphasized that IPM, as an ecological method and environmentally friendly technology, is a multi-faceted approach to pest management that seeks to minimize the negative impacts on the environment. Therefore, it is evident that farmers with IPM experience consider environmental criteria more important when selecting and using pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated pest management is a dynamic and constantly evolving approach to crop protection in which all the suitable management tactics and available surveillance information are utilized to develop a holistic management program. Sustainable pest management aims to minimize the destruction of the natural environment and achieve a high and profitable yield [ 164 ]. PSMs are natural products that are effective against insect pests.…”
Section: Role Of Plant Secondary Metabolites In Sustainable Crop Prot...mentioning
confidence: 99%